Performance Study of Influence of Man-in-the-Middle Attack on AODV Routing Protocol - Nurfarahain, Jamel (Universiti Malaysia Sarawak (UNIMAS), 2015)
As networks grow and incorporate more sophisticated technologies, it can become difficult to maintain the necessary situational awareness. In today internet environment, there is an enormous daily increase of network attacks. The data transferring over the network needs to be more secure. Nowadays, the number of data generate from various resources such as social media produce high volume of data and increases each day. Security for the data being send and receive is very crucial at existing era, especially once it comes to wireless environment. Authentication of critical data is always at risks through wireless network due to its lack of physical nature of wireless environment. Some researchers have discussed about the security managements in wireless network environment, a very few have try to see the influence of basic wireless network security issues on AODV routing protocol Many unknown attacks and threats may occur if the security of the network can be easily broken. Throughout this research project we will do a performance study of influence of Man-in-the-Middle attack on AODV routing protocol.